Comment on "A temporal accessibility model for assessing the ability of search and rescue in Nansha Islands, South China Sea" by Wei et al., Ocean & Coastal Management 95 (2014) 46–52. (15th March 2017) - Wang, Nuo; Lin, Wan-Ni; Wu, Nuan; Song, Nan-Qi; Liu, Zhong-Bo
Abstract: According to the paper byWei et al. (2014), the assumption of the search and rescue (SAR) bases of Chinese patrol vessels does not conform to the current reality. This renders the probability distribution of Chinese patrol vessels in the South China Sea to be inaccurate; The selection of the count and speed of Chinese patrol vessels does not conform to the current reality either, which results in incorrect calculation results of the SAR time. Given the aforementioned issues, the temporal accessibility model in the paper should be improved, and the conclusions should be adjusted accordingly.